Doxorubicin kinetics and effects on lung cancer cell lines using in vitro Raman micro‐spectroscopy: binding signatures, drug resistance and DNA repair. Issue 1 (21st June 2017) - Farhane, Zeineb; Bonnier, Franck; Howe, Orla; Casey, Alan; Byrne, Hugh J.
Abstract: Raman micro‐spectroscopy is a non‐invasive analytical tool, whose potential in cellular analysis and monitoring drug mechanisms of action has already been demonstrated, and which can potentially be used in pre‐clinical and clinical applications for the prediction of chemotherapeutic efficacy. To further investigate such potential clinical application, it is important to demonstrate its capability to differentiate drug mechanisms of action and cellular resistances. Using the example of Doxorubicin (DOX), in this study, it was used to probe the cellular uptake, signatures of chemical binding and subsequent cellular responses, of the chemotherapeutic drug in two lung cancer cell lines, A549 and Calu‐1. Multivariate statistical analysis was used to elucidate the spectroscopic signatures associated with DOX uptake and subcellular interaction. Biomarkers related to DNA damage and repair, and mechanisms leading to apoptosis were also measured and correlated to Raman spectral profiles. Results confirm the potential of Raman spectroscopic profiling to elucidate both drug kinetics and pharmacodynamics and differentiate cellular drug resistance associated with different subcellular accumulation rates and subsequent cellular response to DNA damage, pointing towards a better understanding of drug resistance for personalised targeted treatment. Abstract : Raman micro‐spectroscopy is employed to investigate and compare Doxorubicin mechanisms of action, its kinetics and different cellular resistances of cancer cell lines A549 and Calu‐1. Results show the potential of Raman not only to distinguish the different mechanisms of action at subcellular level but also to elucidate drug resistance by increase tolerance to DNA damage and higher DNA repair.